Do the World Health Organization's social determinants of health predict the mental health trajectories of young Australians? A policy-focused analysis - Manohar, Narendar; Fujimoto, Hiroko; Harvey, Samuel B; Mackinnon, Andrew; Baldwin, Peter A (My University, 2025)
Mental health disorders are concerningly high among young people, with one in five beginning in early childhood. This study examined developmental trajectories of internalising and externalising symptoms in young Australians and identified social determinants that best predict these psychiatric symptom trajectories. Data from 5514 children in the Longitudinal Study of Australian Children were analysed. Group-based trajectory modelling identified symptom trajectories using Strengths and Difficulties Questionnaire scores across seven age-points. Multinomial logistic regression models examined associations between social determinants (guided by WHO Commission on Social Determinants of Health framework) and trajectory class membership. A total of 5501 children (2718 B-cohort; 2783 K-cohort) were included. Three distinct trajectories were identified for both internalising and externalising symptoms. For internalising symptoms, two groups maintained 'normal' levels, while one exhibited progressively worsening 'abnormal' levels. For externalising symptoms, two groups remained 'normal', while one exhibited persistent 'abnormal' levels despite declining. Key social determinants included socio-economic status, biological sex, maternal depression, hostile/angry parenting, partner violence, maternal smoking and social connections. Population Attributable Fractions suggest that reducing maternal depression, angry parenting and partner violence could prevent up to 40% of abnormal symptom trajectories, while higher socioeconomic position and maternal social connectedness may offer modest protection. Nearly 10-15% of adolescents followed abnormal symptom trajectories from early childhood. Reducing maternal depression, angry parenting and partner violence, and enhancing maternal social connectedness could substantially prevent these trajectories. Addressing these social determinants through targeted policies aligned with the WHO-CSDH framework is essential for improving youth mental health.
Aust N Z J Psychiatry
Keywords: Internalising; World Health Organization; externalising; mental health policy; social determinants; trajectories; Adolescents and youth; Childhood and child development; Health and wellbeing